Electrochemical analysis of the dissolution of gold in a copper–ethylenediamine–thiosulfate system - Xiang Peng-Zhi; Liu Qiong; Deng Chao; Ye Guo-hua (Green Processing and Synthesis, 2023)
Thiosulfate gold leaching is a green gold extraction technology. Here, the effects of thiosulfate, copper ion, ethylenediamine, and polarization voltage on the dissolution of gold in this system were investigated by an electrochemical method. The results showed that the addition of thiosulfate promoted the dissolution of gold, but increasing the thiosulfate concentration had a little additional effect. The addition of ethylenediamine also increased the dissolution of gold, but the dissolution resistance of gold increased after adding ethylenediamine. The dissolution of gold increased, the diffusion resistance increased, and the dispersion effect increased upon increasing the copper ion concentration. The copper–ethylenediamine–thiosulfate system did not display passivation (or only weak passivation) upon increasing the polarization voltage, which indicates that the system was relatively stable. The influence of three factors on the dissolution of gold followed the order thiosulfate > copper ion > ethylenediamine.